Rights of fetus in Muslim jurisprudence - Shuriye, Abdi Omar (Islamic Centre for Research and Development, Australia, 2008)
Fetus is a later phase of the unborn offspring. It is a scientific term coined to describe the period of the unborn after the embryonic stage. From the conception to the eighth week the development of the offspring is known as embryo. Muslim Jurisprudence regards the Janin (Fetus) as the first unit of human being; as such, it grants protection and reverence, it also confers a wide range of rights in order to safeguard the development, welfare and the security of the fetus.